Early-life stature, preschool cognitive development, schooling attainment, and cognitive functioning in adulthood: a prospective study in four birth cohorts - Stein, AD; Adair, LS; Donati, G; Wray, C; Richter, LM; Norris, SA; Stein, A; Martorell, R; Ramirez-Zea, M; Menezes, AMB; Murray, J; Victora, C; et al. (Elsevier, 2023)
Background Nutrition is important for growth and brain development and therefore cognitive ability. Growth faltering in early childhood, an important indicator of early adversity, is associated with poorer developmental outcomes, some into adulthood, but this association probably reflects early-life deprivation. We aimed to investigate the associations between early-life stature, child IQ, and adult IQ.